Pengaruh Buah Kelapa Sebagai Faktor Keberhasilan Produksi Virgin Cocount Oil Secara Fermentasi Menggunakan Minyak Pancingan - sawo, agustina; Tukan, Gerardus D. (Jurnal Teknologi Pertanian (Agricultural Technology Journal), 2023)
The production of virgin coconut oil by the community is carried out using various techniques. One of them is fermenting using pure coconut oil as an inducement oil. However, production failures often occur. This study aims to examine the condition of coconut fruit as one of the success factors in production. There were 3 types of test samples, namely old coconuts (A), old coconuts containing kentos (B) and half-ripe coconuts (C). Production is carried out using the fermentation method and virgin coconut oil is used as the cooking oil. The three types of samples were treated the same, namely the volume of coconut milk, the volume of castor oil, the condition of room temperature and the length of time fermentation. The test was carried out 5 times for each sample. The success of the fermentation is indicated by the separation of the oil from the water and blondo. The results showed that of the 5 times of production, the highest production success occurred in sample A, which was 87%, while sample B was 40% and sample C was 20%. It was concluded that production using coconut milk from old coconuts (sample A), had a higher production success rate compared to coconut milk from B and samples C.